The Iliad, the Odyssey, and narratological intertextuality - Currie, BGF (Taylor and Francis, 2019)
This paper discusses four distinctive Homeric narrative features where an intertextual relationship between the Iliad and the Odyssey can be discerned: (1) the narrator's choice to begin the narration mid-fabula, pitching the narratee in medias res; (2) the narrator's initial declaration of a theme in the proem and the subsequent duplication of that theme in the course of the narrative; (3) the creation of a sense of narrative closure through scenes involving fathers, and a related use of fathers as unseen characters in the narrative; and (4) the use of interlaced storylines and of a related continuity of time principle. The poet of the Odyssey must be understood on several occasions to recur not to any quasi-transcendental repertory of narratological techniques, but to the narratological techniques that were specifically deployed in the Iliad.